2009
DOI: 10.1016/j.virol.2009.03.034
|View full text |Cite
|
Sign up to set email alerts
|

Two adjacent mutations on the dimer interface of SARS coronavirus 3C-like protease cause different conformational changes in crystal structure

Abstract: The 3C-like protease of SARS coronavirus (SARS-CoV 3CL(pro)) is vital for SARS-CoV replication and is a promising drug target. It has been extensively proved that only the dimeric enzyme is active. Here we discovered that two adjacent mutations (Ser139_Ala and Phe140_Ala) on the dimer interface resulted in completely different crystal structures of the enzyme, demonstrating the distinct roles of these two residues in maintaining the active conformation of SARS-CoV 3CL(pro). S139A is a monomer that is structura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
116
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(129 citation statements)
references
References 51 publications
10
116
1
2
Order By: Relevance
“…By use of overlapped residues such as Tyr126, dimerization becomes elegantly coupled to catalysis of the SARS-CoV 3C-like protease. Indeed, despite having mutation residues at very different locations, three monomeric mutants G11A , S139A (Hu et al, 2009) and R298A (Shi et al, 2008) available so far all share highly-superimposable backbone structures, in which the characteristic short 3 10 -helix forms within the region Ile136-Gly143 of all three mutants ( Fig. 3D).…”
Section: Inactivation Of the Catalytic Machinery By Structurally-drivmentioning
confidence: 99%
See 1 more Smart Citation
“…By use of overlapped residues such as Tyr126, dimerization becomes elegantly coupled to catalysis of the SARS-CoV 3C-like protease. Indeed, despite having mutation residues at very different locations, three monomeric mutants G11A , S139A (Hu et al, 2009) and R298A (Shi et al, 2008) available so far all share highly-superimposable backbone structures, in which the characteristic short 3 10 -helix forms within the region Ile136-Gly143 of all three mutants ( Fig. 3D).…”
Section: Inactivation Of the Catalytic Machinery By Structurally-drivmentioning
confidence: 99%
“…It is also surprised to find that although the dimeric SARS-CoV 3C-like protease has a very large dimeric interface area of over 1000 Å 2 , one single interfacial mutation such as Gl1A within the chymotrypsin fold (Chen et al, 2016;Hu et al, 2009), and R298A within the extra domain is sufficient to eliminate the dimerization. Most amazingly, it has been also shown that the residues for controlling dimerization are not just limited to the interfacial ones, because residues located away from the dimerization interface was also identified to be crucial for dimerization (Barrila et al, 2006(Barrila et al, , 2010.…”
Section: Inactivation Of the Catalytic Machinery By Structurally-drivmentioning
confidence: 99%
“…Critical N-terminal amino acid residues up to Arg-4 and C-terminal residues up to Gln-299 have been identified as involved in dimerization and thus in generating the correct conformation of the active site (17,18). In addition, the interactions between the two helices A 0 (residues [11][12][13][14][15] and the S1 substrate-binding subsite, consisting of Phe-140, His-163, Met-165, Glu-166, and His-172, are also regarded as major components of the dimer interface (19,20).…”
Section: Introductionmentioning
confidence: 99%
“…Compared with functional dimeric Mpro, the crystal structures of monomeric Mpro (G11A, S139A, and R298A) have provided direct structural evidence for the catalytic incompetence of the dissociated monomer (19)(20)(21). In the monomer mutants, the oxyanion loop (Ser-139 to Leu-141) is converted into a short 3 10 -helix and completely collapses inward, as exemplified by the large movement of Asn-142 and Leu-141.…”
Section: Introductionmentioning
confidence: 99%
“…[23] Other vital component of S1 subsite is the oxyanion hole, formed by the interaction of carboxylate anion of the conserved Gln with Gly143, Ser144 and Cys145, which stabilizes the transition state during proteolysis. [24,25] Glu166 at the entrance of the pocket interacts via H-bond with Nɛ2 of the conserved 7 Gln. [24] The S2 and S4 subsites contain hydrophobic and bulky side chains like Val, Leu or Phe.…”
Section: Resultsmentioning
confidence: 99%